The Influence of Person-Organization Fit, Motivation, and Trust on Knowledge Sharing Moderated by Transformational Leadership at the Islamic Education Welfare Foundation (YAKPI) Susukan, Cirebon Regency - Najih, Shofiyuddin; Rizal, Alimuddin (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the effects of Person-Organization Fit, motivation, and trust on knowledge sharing behavior, with transformational leadership as a moderating variable. The study involved 140 teachers from the Islamic Education Welfare Foundation (YAKPI) in Susukan, Cirebon. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results revealed that motivation significantly affects knowledge sharing, while Person-Organization Fit and trust do not. Transformational leadership moderates the effect of motivation but weakens its influence. These findings underline the critical role of leadership in fostering knowledge sharing within educational institutions.